Serum γ-glutamyltransferase and the risk of heart failure in men and women in Finland. Issue 3 (9th November 2012) - Wang, Yujie; Tuomilehto, Jaakko; Jousilahti, Pekka; Salomaa, Veikko; Li, Bin; Antikainen, Riitta; Mähönen, Markku; Katzmarzyk, Peter T; Hu, Gang
Abstract : Objectives: To evaluate the association of serum γ-glutamyltransferase (GGT) levels with heart failure (HF) risk in the Finnish population. Design: Prospective population-based cohort study. Setting: The present study, which is a part of FINRISK study, was carried out in Finland. Subject study cohorts included 18 353 Finnish men and 19 726 women who were 25–74 years of age and free of HF at baseline. Main outcome measures HF (636 men and 445 women) during a mean follow-up of 14.5 years. Results: Baseline measurement of different levels of serum GGT was used to predict incident HF. The multivariable-adjusted (age, sex, study area, study year, smoking, education, alcohol consumption, physical activity, valvular heart disease, body mass index (BMI), systolic blood pressure, total cholesterol at baseline, myocardial infarction and diabetes at baseline and during follow-up) HRs of HF at five GGT groups (using the 25th, 50th, 75th and 90th percentiles) were 1.00, 1.16 (95% CI: 0.97 to 1.38), 1.20 (1.00 to 1.45), 1.29 (1.04 to 1.60) and 1.82 (1.45 to 2.29) (Ptrend <0.001). Stratification by smoking status, alcohol consumption and BMI gave similar results, while stronger association was observed among subjects aged <60 years (Ptrend =0.001) compared with subjects 60+ years of age (Ptrend =0.173). Conclusions: Moderate to high levels of serum GGT (from the 50th to the 90th percentiles) were significantly associated with incident HF in men and women in Finland, and the predictive power was stronger in subjects aged <60 years.